Fatti e interpretazioni. Cinquant’anni di pensiero nuovo - De Simone, Gianfranco (Il sogno della farfalla, 2012)
The article follows on from a polemical call by some philosophers to return to Realism in philosophy after decades of postmodern and weak thought that had banished the reality of facts and said goodbye to truth. According to supporters of New Realism, the primacy of interpretations over facts had not delivered the liberating results foreseen by the postmodernists, rather it had given men in power an alibi for the theoretical construction of truth aimed at covering up their abuses of power. What is highlighted is the fact that by turning one’s back on facts one not only runs into ethical and political questions, but affects fundamental aspects in medicine where the impossibility of ascertaining facts leads to the impossibility of providing a cure, and above all in psychiatry where it becomes impossible to distinguish between a delusion and a thought which can lead to knowledge and therefore a cure to mental illness. The article also examines the theoretical and historical implications of the main philosophical positions which have led, in the name of an impossibility to know the origin of thought and the truth of human nature, to a denial of the legitimacy of a psychiatric identity. In opposition to all this, the solitary and then collective walk of a psychiatrist who has arrived at a new thought able to propose a theory about human nature and a psychotherapy able to offer a cure.